2005
DOI: 10.2478/bf02475617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electron irradiation on the optical properties of the natural armenian zeolite-clinoptilolite

Abstract: Abstract:Infrared (IR) absorption and luminescence in chemically and radiationmodified natural Armenian Zeolite (clinoptilolite) samples have been studied. The luminescence was studied in 390-450 nm and 620-710 nm wavelength bands, and the IR measurements were carried out in the 400-5400 cm −1 range. It is shown that the luminescence intensity depends on the content of pure clinoptilolite in the samples and, probably on the distribution of "passive" luminescence centers over Si and Al sites that became "active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Luminescence properties of natural CZs were investigated earlier, and the UV-blue (220 to 420 nm) band with maximum at around 280-nm excitation spectrum and broad emission band (300 to 600 nm) were observed. [13][14][15] It was demonstrated that CZ luminescence depended on local defects and imperfections in crystals. 13 Substitution of Fe 3þ ions with ions of other metals formed the centers of luminescence, and high correlation in the emission intensity around 350 nm with the Fe 3þ concentration was observed in the specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescence properties of natural CZs were investigated earlier, and the UV-blue (220 to 420 nm) band with maximum at around 280-nm excitation spectrum and broad emission band (300 to 600 nm) were observed. [13][14][15] It was demonstrated that CZ luminescence depended on local defects and imperfections in crystals. 13 Substitution of Fe 3þ ions with ions of other metals formed the centers of luminescence, and high correlation in the emission intensity around 350 nm with the Fe 3þ concentration was observed in the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, intensity increase in photoluminescence with the enrichment of CZ in raw mineral or during irradiation of the CZ samples by low dose of accelerated electrons (8 MeV) was observed. 15 The formation of luminescence centers was explained by radiation-induced change of the lattice ions and emergence of oxygen-cation vacancy. However, the scattering and linear absorption of zeolites samples are very strong in the UV spectral region and hinder to perform conventional spectroscopic measurements or optical imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The radiolytic and displacement effects on adsorbed water must also be considered. A radiation dose of 3·10 16  electron/cm 2 at an energy of 8 MeV appears critical to promote structural changes in these natural zeolite samples, which is signified by a pronounced variation in the dielectric properties and optical characteristics of the materials910.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms by which ZL materials have achieved success in pharmacology and health-care are not well understood, and optical imaging tools applied to ZL can help to understand some of mechanisms of these processes and make a significant contribution to biomedical and pharmacological applications of ZLs. Photoluminescence of natural ZLs were observed and investigated previously 25 26 27 28 , and it was shown that the majority of ZL types had characteristic excitation spectrum in 220–420 nm range with the maximum position around 300 nm, and emission spectrum in 280–600 nm spectral range. Furthermore, it was shown that luminescent properties of ZL were very much dependent on imperfections (or local defects) in crystals 25 .…”
mentioning
confidence: 99%
“…In addition to this de-alumination, the following imperfections and factors also could be responsible for luminescence of ZL: phonon, electron and hole excitons, interstitial atoms and ions, decationization and dehydroxylation 25 . Moreover, it was shown that the photoluminescence intensity increased with the enrichment of clinoptilolite in row zeolites or when the CZ samples were irradiated by low dose of accelerated electrons with 8 MeV energy 27 . The appearance of new luminescence centres was explained by radiation-induced change of initial charge states of the lattice ions and formation of oxygen-cation vacancy.…”
mentioning
confidence: 99%